Body-earth between Collapses and Refugio - Azambuja, Katiuska (2024)
Refúgio is a performative work carried out with women in the city of Várzea Grande, Brazil, in 2023. The proposal develops in poetic stages, composed of drawings, sounds, letters, and video art. This reflection is based on the text The Burnout Society (Han, 2015) relating to climate collapse. Based on it, we ask ourselves how to have a radically alive life, evoking the ideas of Ailton Krenak (2020) and Dènetém Bona (2020). The objective was to activate listening to the body-earth, an expression by artist Ana Mendieta, in relation to the idea of the Earth-Body, bringing the original concept of aisthesis, a term in which building decolonial subjectivities (Mignolo, 2011). These ideas go beyond the culture-nature duality (Mignolo, 2017) and resume the perception of nature as a living being and the ancient relationships that sustain life and humanity (Walsh, 2008). Cartography was chosen as a methodological tool, as it is an anti-method that requires careful attention to forming subjectivities while the need to follow processes requires inhabiting an existential territory (Barros & Kastrup, 2015). From the creation exercises, the participants revealed a more attentive perception of rhythm/space, and a greater awareness of listening to the body-earth and the earth-body.